Strategi Pasar dan Pemasaran pada Gooprex Poultry and Shop Diponegoro - Putra, Gilang Chaya (Maliki Interdisciplinary Journal, 2025)
Gooprex targets local farmers and housewives by offering quality products at affordable prices, and utilizing online promotions via WhatsApp and Facebook, as well as traditional word-of-mouth methods. Despite facing competition, Gooprex has managed to take advantage of market conditions to continuously improve the quality of its services and reach a wider range of consumers. Careful market analysis and innovation strategies have enabled the business to survive and thrive amidst challenges. By focusing on customer relationships, product availability, and adapting to local needs, Gooprex has succeeded in creating customer loyalty. In the future, product diversification and expansion of the distribution network can be the main drivers of the growth of this business as a major player in the distribution of animal feed and eggs in the Diponegoro area.